The occupational syndemics of miners in South Africa - Nicola Bulled; Merrill Singer (Springer, 2024)
Abstract Occupational exposures in the large industrial mining sector contributed significantly to South Africa's high excess death rate due to COVID-19. Historically poor work-protection oversight has perpetuated centuries of risky labor and living conditions within the industry, driving high levels of disease co-morbidities, and supporting enduring social vulnerabilities. In this paper, we offer a syndemic lens to consider the clustering of adversely interacting diseases among mineworkers in South Africa, drawing attention to the complex occupational health crisis and the need to move beyond simply reporting individual diseases or comorbidities among this population. The physically demanding and dangerous working conditions, the lack of adequate changes to crowded and unsanitary working and living situations, the failure to meet social and labor plan targets, the continued precarious nature of working contracts and mines, and the limited access to robust healthcare reflect the historically exploitative nature of industrial mining in South Africa that places miners at increased risk for various syndemics. This assessment of the adverse interactions of diseases and socioeconomic and political conditions highlights the need for focused research and more follow-through in comprehensive occupational reforms.